THE IMPACT OF GLOBALIZATION PROCESSES ON THE TRANSNATIONALIZATION OF BANKING ACTIVITY - Момот , Олександр (Socio-economic relations in the digital society, 2019)
The sense of globalization processes in the fi nancial sphere is disclosed. The internalization and eclectic paradigms of the emergence of transnational corporations are compared. The tendencies of development of the banking sector in the conditions of globalization processes are revealed. Dialectical unity and contradictions of interests of global economic entities and states are shown. Th e infl uence of the processes of transnationalization of bank capital on national banking systems is assessed. Th e positive impact of fi nancial globalization on national banking systems consists of: increased competition between banks; growth in the profi tability of the banking sector with a smaller margin; transfer of advanced technologies; increase in labor productivity; diversifi cation of sources of fi nancing; increased stability during pe riods of crisis; growth of lending to the national economy. The negative consequences of fi nancial globalization for national banking systems are manifested in the following: a violation of the stability of the banking system; changes in the conditions of functioning of local banks due to strong competition from transnational banks; deterioration in the quality of loan portfolios of local banks; the seizure by foreign banks of the most promising segments of the banking services market.